Sistematicidad y técnica legislativa en materia penal: un estudio a partir de los delitos nucleares de la Ley de Tránsito chilena - Mayer Lux, Laura; Vera Vega, Jaime (Pontificia Universidad Católica del Perú, 2022)
The objective of this paper is to examine the principle of systematicity as a criterion of an adequate legislative technique in criminal matters, regarding the norms that regulate nuclear crimes of vehicular traffic in Chile. The analysis focuses on the rule that establishes the effective enforcement of the custodial sentences imposed on some of these crimes, which breaks with the system of crimes regulated in Chile, that is generally based on another class of criminal reactions. The study uses fundamentally a dogmatic methodology and a recourse to legal, jurisprudential and doctrinal sources. Among its results, the article highlights the relevance that the principle of systematicity has for the creation of criminal laws, either as such or in relation to other principles of law, like equality before the law, proportionality or certainty. It also concludes that the violation of the principle of systematicity affects both formal and substantive aspects, that is, relative to the instruments that serve as a source for criminal norms and their content.

El objetivo del presente trabajo es examinar el principio de sistematicidad como criterio de una adecuada técnica legislativa en materia penal, en relación con las normas que regulan los delitos nucleares del tráfico vehicular en Chile. El análisis se centra en la regla que establece el cumplimiento efectivo de las penas privativas de la libertad impuestas a algunos de esos ilícitos, la cual rompe con la sistemática de los delitos consagrados en Chile, que se sustenta de forma general en otra clase de reacciones penales. El estudio utiliza una metodología fundamentalmente dogmática y un recurso a fuentes legales, jurisprudenciales y doctrinales. Entre sus resultados, destaca la relevancia que el principio de sistematicidad tiene para la creación de leyes penales, ya sea en cuanto tal o en relación con otros principios del derecho, como los de igualdad ante la ley, proporcionalidad o certeza. El artículo concluye, asimismo, que la afectación del principio de sistematicidad incide tanto en aspectos formales como sustantivos; o sea, relativos a los instrumentos que sirven de fuente a las normas penales y al contenido de estas.
Systematicity and Legislative Technique in Criminal Matters: A Study Based on the Nuclear Crimes of the Chilean Traffic Law
Keywords: Zero tolerance; Innocuation; Custodial punishment; Alternative punishment; Equality before the law; Proportionality; Certainty; Tolerancia cero; Inocuización; Penas privativas de la libertad; Penas sustitutivas; Igualdad ante la ley; Proporcionalidad; Certeza; https://purl.org/pe-repo/ocde/ford#5.05.01